IMPROVEMENT OF DRAINAGE AS ONE OF THE SOLUTIONS FOR FLOOD CONTROL IN RT 12 RW 06 CAKUNG PENGGILINGAN EAST JAKARTA - Cahyo Wibowo; Dibyo Setiawan; Fathan Mubina Dewadi; Bantu Hotsan S (International Journal of Engagement and Empowerment, 2021)
Flooded is a classic thing in every area, especially in the capital city. Floods in Jakarta cannot be separated from the role of the community in urban areas and villages within the town. People's behavior in everyday life, the condition of infrastructure in the community is critical in overcoming flood problems and external causes such as high rainfall, global warming, and climate change. People's behavior that ignores environmental cleanliness such as littering, changing the function of infiltration land as a residence without thinking about environmental impacts, community participation in the maintenance, and lack of concern for the condition of drainage infrastructure in the environment has a vital role. The absence of supervision, respect and local government's role is also one of the causes of the poorly maintained drainage system in settlements